Virtual school - Franciszek Szlosek (Institute of Social Affairs of the Pedagogical University of Cracow, 2021)
The article deals with the issue of virtual school as a kind of alternative to the traditional classroom system of teaching. The introduction attempts to clarify the meaning of several terms that are essential for this subject field, including the concept of virtual reality and, of course, virtual school. First of all, the essence and types of virtual schools are discussed, with an articulation of the advantages of virtual education. The professional competencies of a virtual school teacher have also been touched upon briefly. Key words: classroom system, traditional school, virtual reality, virtual school, teachers' professional competencies, teachers' IT competencies Szkoła wirtualna W artykule podjęta została problematyka szkoły wirtualnej jako swoistej alternatywy wobec tradycyjnego klasowo-lekcyjnego systemu nauczania. Na wstępie starano się wyjaśnić znaczenie kilku zasadniczych dla tej tematyki terminów, w tym pojęć rzeczywistości wirtualnej i oczywiście szkoły wirtualnej. Przede wszystkim omówiono istotę i rodzaje szkół wirtualnych z wyartykułowaniem zalet wirtualnego kształcenia. Sygnalnie zostały również zaprezentowane kompetencje zawodowe nauczyciela szkoły wirtualnej.